PEMANFAATAN FUNGI MIKORIZA ARBUSKULA LOKAL DAN TANAMAN INANG Desmodium spp. UNTUK MENINGKATKAN PERTUMBUHAN BIBIT CENDANA (Santalum album Linn.) Utilization of Local Arbuscular Nyhorrizhal Fungi (AMF) and Desmodium spp. Host Plants on Promoting Sandalwood - Abdonia W. Finmeta; Irdika Mansur; Arum Sekar Wulandari (Jurnal Silvikultur Tropika, 2018)
Sandalwood (Santalum album Linn.) is one of important native tree species in East Nusa Tenggara, slow-growing species with high economic value. The aims of this research were to analyze the effectiveness of local AMF inoculum andutilization of host plants to improve the growth of Sandalwood seedlings in the nursery. The research used complitely randomised design (CRD)-split plot design where origin of AMF soil inoculum as the main plot namely control (M0), soilinoculum from Nano Vilage (M1), HTC Bu’at (M2) and Demplot Cendana Sisismeni (M3). While the host plants as the sub-plot, consist of control no host plant (T0), Desmodium ovalifolium (T1), Desmodium heterophyllum (T2) andAlternanthera sp. (T3). The result showed that the local AMF and host plants applications effectively improved Sandalwood seedling growth, especially in heigth, number of leaves and diameter. The best interaction of soil inoculumfrom HTC Bu’at and D. heterophyllum (M2T2) increased plant height, number of leaves, diameter, shoot dry weight (BKP), root colonization, shoot root ratio (NPA) and seed quality index (IMB) compared with control. Soil inoculuminteraction from HTC Bu’at and D. heterophyllum host plants were exellent for improved the quality of Sandalwood seedlings.Key words : Alternanthera, arbuscular mychorrizhal fungi, Desmodium, sandalwood